1999
DOI: 10.2169/internalmedicine.38.336
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human Leukocyte Antigen Class II Genes with Autoantibody Profiles, but not with Disease Susceptibility in Japanese Patients with Systemic Sclerosis.

Abstract: Object: To examine the role of human leukocyte antigen (HLA) class II genes in the development of systemic sclerosis (SSc) as well as in the clinical and serologic expression of SSc in patients. Methods: HLA-DRB1, DRB3, DRB4, DQB1, and DPB1 alleles were determined by genotyping; and serum antinuclear antibodies were identified using indirect immunofluorescence, double immunodiffusion and immunoprecipitation. Patients: One hundred and five Japanese patients with SSc and 104 race-matched healthy controls. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 37 publications
3
46
0
7
Order By: Relevance
“…Nevertheless, even these associations have been reported to belong into autoantibody positive subgroups rather than the overall disease (e.g., HLA-DRB1*1104), hence supporting the hypothesis that MHC class II genes associations observed in the overall disease are residual from the autoantibody positive subgroups. Furthermore, Kuwana et al (1999) suggested that the associations within the xMHC of HLA class II genes was exclusively conWned to the autoantibody proWles and not to the disease susceptibility, in contrast to the Wndings in the more recent works (Arnett et al 2010;Simeon et al 2009). Hence, most of the strongest associations are found within the major autoantibody positive subgroup of patients ( Table 2).…”
Section: Hla Genesmentioning
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, even these associations have been reported to belong into autoantibody positive subgroups rather than the overall disease (e.g., HLA-DRB1*1104), hence supporting the hypothesis that MHC class II genes associations observed in the overall disease are residual from the autoantibody positive subgroups. Furthermore, Kuwana et al (1999) suggested that the associations within the xMHC of HLA class II genes was exclusively conWned to the autoantibody proWles and not to the disease susceptibility, in contrast to the Wndings in the more recent works (Arnett et al 2010;Simeon et al 2009). Hence, most of the strongest associations are found within the major autoantibody positive subgroup of patients ( Table 2).…”
Section: Hla Genesmentioning
confidence: 88%
“…Hence, most of the strongest associations are found within the major autoantibody positive subgroup of patients ( Table 2). The most solid, replicated associations with the autoantibody subgroups are the HLA-DQB1*0501/HLA-DRB1*0101 haplotype with the production of ACA (Arnett et al 2010;Simeon et al 2009;Kuwana et al 1999;Kuwana et al 1995), HLA-DRB1*1104 and HLA-DPB1*1301 with the production of ATA (Simeon et al 2009;Gilchrist et al 2001;Fanning et al 1998) and HLA-DQB1*0302 with the production of ARA (Arnett et al 2010;Kuwana et al 1999). It is noteworthy that the Wrm association of the absence of a polar aminoacid in the position 26 of the HLA-DQB1 molecule with the presence of ACA which has been only found in populations of Caucasian origin (Arnett et al 2010;Gilchrist et al 2001;McHugh et al 1994;Beretta et al 2011).…”
Section: Hla Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon this observation, Rosen and colleagues (23) have noted that heavy metals also are concentrated in the nucleolus and may catalyze oxidative reactions or in other ways fragment these proteins and reveal cryptic epitopes vulnerable to initiating an autoimmune response. It is likely that CD4-positive T lymphocytes are involved, because each of these autoantibody responses is associated with specific and largely different MHC class II alleles (2,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Während eine enge Korrelation von typischen HLA-Markern zu bestimmten Autoantikörperprofilen bei der progressiven systemischen Sklerodermie für eine vererbbare genetische Prädis-position spricht [8,11,12], deutet für die primäre biliäre Zirrhose nur die erhöhte Prävalenz der Erkrankung bei Familienangehörigen (4,28 : 100 000) gegenüber der normalen Bevölkerung (0,7-7,5 : 100 000) einen genetischen Hintergrund an [10].…”
unclassified